Haematological and obstetric aspects of antenatal diagnosis of beta-thalassaemia: experience with 200 cases. Issue 2 (April 1982) - Cao, A; Furbetta, M; Angius, A; Ximenes, A; Rosatelli, C; Tuveri, T; Scalas, M T; Falchi, A M; Angioni, G; Caminiti, F
Abstract : The results of 200 antenatal diagnoses in pregnancies at risk for homozygous beta-thalassaemia, carried out on fetal blood samples obtained by placental aspiration in the second trimester, are described. Globin chain synthesis in the fetuses was measured by means of 3H-leucine incorporation and separation of the chains on carboxy-methyl-cellulose columns. Fetal red cell enrichment was performed by NH4Cl-NH4HCO3 differential lysis of maternal cells or anti-i differential agglutination. Sufficient fetal blood for analysis was obtained in 97.5% of the cases. The overall fetal loss rate was 6.5%, but it declined from 10% in the first consecutive 100 cases to 3% in the last 100 cases. Fetal loss was the result of early or late intrauterine death or spontaneous abortion. Forty-two homozygous fetuses had no beta-chain synthesis and one had a very low beta/gamma ratio (0.005). Of the pregnancies, 37 were terminated at parental request and four aborted spontaneously. Absence of beta-chain radioactivity was confirmed in 12 abortuses with suitable cord blood samples for analysis. Two pregnancies with homozygous fetuses were not terminated, as one member of each couple was a devout Catholic. As expected, both infants developed Cooley's anaemia. Follow-up of the 146 infants, diagnosed in utero as non-homozygotes, showed cerebral palsy in one and a small cutaneous needle injury in three. None of these developed homozygous beta-thalassaemia. Even beta-thalassaemia trait with a beta/gamma ratio of 0.046 +/- 0.012 can be distinguished from normal, showing a beta/gamma ratio of 0.086 +/- 0.019 with a high degree of certainty.